Comparative accuracy evaluation of patient-specific 3D-printed guide and neuronavigation for ventriculoperitoneal shunt in dogs: a dual-phase ex vivo and in vivo study - Jeon, YoungJin; Cho, Cheongwoon; Jeong, Jaemin; Meij, Björn; Lee, Haebeom (Frontiers in Veterinary Science, 2025)
BackgroundVentriculoperitoneal shunting (VPS) is an effective treatment for canine hydrocephalus, but complications related to ventricular catheter (VC) misplacement remain a concern. Although neuronavigation improves accuracy, its cost and complexity limit veterinary use. Patient-specific 3D-printed guiding systems (PS-3DGS) offer a potential alternative.ObjectivesTo compare the accuracy and feasibility of PS-3DGS compared to electromagnetic neuronavigation for VC placement in 3D-printed canine cranio-ventricular models (CVMs) and Beagle dogs.Animals and study designTen 3D-printed CVMs (ex vivo study) and five experimental Beagle dogs (in vivo study).MethodsVC placement was performed using PS-3DGS and neuronavigation in CVMs and experimental animals. Accuracy was assessed by the distance from the VC tip to the foramen of Monro (DFM), tip coordinates (X, Y, Z axes), tip placement error, intraventricular insertion length (IIL), and catheter contact with the ventricular wall (VVL). Intraoperative procedural time and anatomical variables, including skull and cranial indices, were also analyzed.ResultsPS-3DGS showed no significant difference in DFM compared to neuronavigation in CVMs and Beagle dogs. PS-3DGS achieved significantly lower VVL and reduced procedural time than neuronavigation in the CVM study (p = 0.011 and p = 0.039, respectively). In dogs, DFM with PS-3DGS was comparable to both neuronavigation and the ex vivo results. Entry point error correlated negatively with cranial index (r = −0.9, p = 0.037).ConclusionPS-3DGS provided accuracy comparable to neuronavigation while simplifying the procedure. It represents a viable, cost-effective alternative for canine VPS surgery, potentially enhancing catheter placement and reducing complications.